Dissemination of Research Findings to Research Participants Living with HIV in Rural Uganda: Challenges and Rewards - Baylor, Anna; Muzoora, Conrad; Bwana, Mwebsa; Kembabazi, Annet; Haberer, Jessica E.; Matthews, Lynn T.; Tsai, Alexander C.; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R. (PLOS Medicine, 2013)
Community participatory research emphasizes communication of study findings to research participants of vulnerable populations [1]. Most dissemination activities in sub-Saharan Africa have occurred after the completion (or termination) of randomized clinical trials of a defined intervention [2–4]. Sharing research findings with participants during observational research can avoid therapeutic misconception [5] as well as evaluate the validity of research involving knowledge, attitudes, or behavior through a ‘‘member check’’ procedure in which investigators conduct interviews regarding the relevancy and saliency of their findings [6]. Nonetheless, the communication of research findings to participants living with HIV enrolled in observational research in a rural sub- Saharan African setting is less straightforward and presents significant challenges with respect to literacy, language, logistics and confidentiality. We communicated research findings to 540 participants enrolled in an ongoing 7- year prospective cohort study of HIV treatment in Mbarara, Uganda. We had not organized prior dissemination meetings. This participant dissemination meeting was motivated in part by feedback from a study participant, who said: ‘‘You have been asking me questions and taking my blood for years but I do not know anything about what you have found.’’ Herein, we describe our first approach to the preparation, logistics, confidentiality concerns, format, participant responses, and follow-up of the dissemination process. Study participants in the Uganda Antiretroviral Rural Treatment Outcomes (UARTO) cohort study are adults living with HIV initiating antiretroviral therapy (ART) at the Immune Suppression Syndrome (ISS) Clinic affiliated with the Mbarara University of Science and Technology (MUST) in rural, southwestern Uganda. The primary objective of the study is to examine the social, behavioral, and economic correlates of long-term adherence to ART using wireless real-time adherence monitoring and to determine the extent to which adherence behavior affects biologic outcomes. We faced several challenges in reporting research findings to this population. Complicated scientific concepts needed to be distilled into simple core messages that could be easily understood—and not misinterpreted—by all participants in the local language (Runyankole), including those with limited formal education. We believed written dissemination would be ineffective since many participants cannot read, and individual oral communication to more than 500 participants is overly resource intensive. Group communication would be complex both in respect to confidentiality and logistics of convening study participants who live within a 60-km radius catchment area in the context of a poor transportation infrastructure. Regardless of the mode and format of communication, accurate translation of scientific concepts from English into Runyankole can be a complicated and lengthy process due to lack of scientific terminology.
Keywords: ART; HIV; Community participatory; Vulnerable populations; Uganda